UMKM BERDAYA BERSAMA DESA WISATA - Realita, Tasnim Nikmatullah; Anggoro, Yudhi (Manajemen & Bisnis Jurnal, 2019)
Village tourism is an alternative development of tourism areas based on local wisdom, people's lifestyles that have shifted towards building harmony with nature are an excellent momentum to start focusing on developing tourist villages. Hard efforts are needed so that the sustainability of the tourism village as an alternative tourist destination can be maintained without ignoring the preservation of nature and social values as the village's fundamental identity. UMKM is a strategic partner that deals in symbiotic mutualism with the tourism village. So the development of tourist villages can not be separated from putting attention to the existing MSMEs. This paper will discuss the synergy of MSMEs with tourism villages through the study of relevant literature Keyword: Desa Wisata, UMKM, Synergy, Local Wisdom